DIVERSIFYING THE PATHWAY: A MULTIFACETED APPROACH WITHIN GEROPSYCHOLOGY. (20th December 2022) - Carpenter, Brian; Ma, Flora; Hiroto, Kimberly
Abstract: Like other health services disciplines, geropsychology is facing a paucity of diverse intersectional identities within a larger shortage of interest in aging across all levels of training. We need an incisive and comprehensive plan to enhance the representation of historically marginalized groups within geropsychology and address systemic factors limiting entrance into the field. In this presentation, we review the projected need for mental health services attuned to equity, diversity, and inclusion and current trends in the geropsychology pathway. Then we describe several initiatives to expand attention to cultural humility and antiracism. These include the development of foundational competencies that include attention to diverse representations, which can be disseminated to pre- and post-licensure generalists and specialists; diversity-infused offerings within recent conferences and webinars; and efforts to intensify the focus on diversity within psychology's aging-related professional organizations. Finally, we conclude with additional suggestions to expand and sustain attention to diversity.